What is multidisciplinary cancer care like in practice? a protocol for a mixed-method study to characterise ambulatory oncology services in the Australian public sector. Issue 10 (10th October 2019) - Nic Giolla Easpaig, Bróna; Arnolda, Gaston; Tran, Yvonne; Bierbaum, Mia; Lamprell, Klay; Delaney, Geoffrey P; Liauw, Winston; Chittajallu, Renuka; Winata, Teresa; Ward, Robyn L; Currow, David C; Olver, Ian; et al.
Abstract : Introduction: An understanding of the real-world provision of oncology outpatient services can help maintain service quality in the face of escalating demand and tight budgets, by informing the design of interventions that improve the effectiveness or efficiency of provision. The aims of this study are threefold. First, to develop an understanding of cancer services in outpatient clinics by characterising the organisation and practice of multidisciplinary care (MDC). Second, to explore the key areas of: (a) clinical decision-making and (b) engagement with patients' supportive needs. Third, to identify barriers to, and facilitators of, the delivery of quality care in these settings. Methods and analysis: A suite of mixed-methods studies will be implemented at six hospitals providing cancer outpatient clinics, with a staged roll-out. In Stage One, we will examine policies, use unstructured observations and undertake interviews with key health professionals to characterise the organisation and delivery of MDC. In Stage Two, observations of practice will continue, to deepen our understanding, and to inform two focused studies. The first will explore decision-making practices and the second will examine how staff engage with patients' needs; both studies involve interviews, to complement observation. As part of the study of supportive care, we will examine the implications of an introduction of patient-reported measures (PRMs) into care, adding surveys to interviews before and after PRMs roll-out. Data analysis will account for site-specific and cross-site issues using an adapted Qualitative Rapid Appraisal, Rigorous Analysis approach. Quantitative data from clinician surveys will be statistically analysed and triangulated with the related qualitative study findings. Ethics and dissemination: Ethical approval was granted by South Eastern Sydney Local Health District Human Research Ethics Committee (no. 18/207). Findings will be shared with participating hospitals and widely disseminated through publications and presentations.